Changes in the Regional Differences of the Labor Market in Hungary During the Millennium Change, Especially the Employment Impact of Financial Crisis in the First Decade of the 21th Century - Zsuzsanna Dabasi Halász (Theory, Methodology, Practice, 2011)
The paper attempts to reveal the causes of labour market inequalities in Hungary after the system change, with special regard to the changes caused by the financial crisis. The current labour market trends were determined by the situation emerged by the time of the regime change, as I will discuss it later. Besides general employment relations, it focuses on changes in social positions and on migration processes and examines what kind of possibilities the crisis and the period afterwards may offer for the development of lagging regions.